EFFECT OF VIDEO PRENATAL YOGA EDUCATION ON PREGNANT WOMEN'S KNOWLEDGE IN TUKADAYA VILLAGE IN 2025 - Gusti Ayu Martha Winingsih; Ni Putu Ayu Rita Cindiani; Luh Verra Sridyantari; Fitria -; Ni Wayan Noviani (STIKES Mamba'ul 'Ulum Surakarta, 2026)
Prenatal Yoga has a positive impact on pregnancy and the fetus, but not all pregnant women are aware of its benefits, necessitating effective counseling methods such as audio-visual videos. The objective of this study was to determine the effect of video-based health education about prenatal yoga on the knowledge level of pregnant women in Tukadaya Village in 2025. This research employed a quasi-experimental design with a one-group pre-test and post-test approach involving 32 respondents selected via purposive sampling. Data collection was conducted using questionnaires before and after the intervention. The results showed that the average knowledge score before the intervention was 72.34 (moderate category) and increased to 88.16 (good category) after the intervention. Analysis using the Wilcoxon test yielded a significance value of p < 0.001 (< 0.05). In conclusion, there is a significant effect of video-based health education about prenatal yoga on improving the knowledge level of pregnant women.